Una tecno-estasi. Tecnicità, magia e simbolismo analogico in Simondon - Revello, Roberto (Mechane, 2025)
The essay explores the relationship between technology, culture, and symbolism in the thought of Gilbert Simondon, highlighting how technology is not alien to the human, but rather an inventive moment of the imago, rooted in the original magical relation between organism and environment. Against the stereotyped opposition between culture and technology, Simondon proposes an ontogenetic and symbolic vision of technicity, where the analogy between technology and sacredness reveals a shared network structure and a common symbolic function. By contextualizing the meaning of magic, the essay advances the hypothesis that Simondon harbors the utopia of a regulating unity capable of restoring soul and beauty to our diverse ways of being in the world–without being able to foresee what now unfolds: the crisis of analogical symbolism.